2002
DOI: 10.1021/jp021401z
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Ion Radiolysis of Liquid Benzene

Abstract: The mechanisms responsible for the main products in liquid benzene radiolysis (biphenyl, molecular hydrogen, and phenyl radical) are probed with protons, helium ions, and carbon ions of a few to 30 MeV energy. Phenyl radical yields have been examined using iodine scavenging techniques. The results are combined with similar data for γ-rays and suggest that phenyl radicals mainly react with benzene to give a long-lived adduct, which leads to polymer formation. Iodine can react with this adduct to give enhanced y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 50 publications
5
56
0
Order By: Relevance
“…The calculated G-values are given in Table 1. These values can be compared to the G-values for degradation of benzene (∼ 0.08 µM/J) [12] and liquid Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/31/15 4:00 AM pyridine (∼ 0.13 µM/J) [13].…”
Section: Resultsmentioning
confidence: 99%
“…The calculated G-values are given in Table 1. These values can be compared to the G-values for degradation of benzene (∼ 0.08 µM/J) [12] and liquid Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/31/15 4:00 AM pyridine (∼ 0.13 µM/J) [13].…”
Section: Resultsmentioning
confidence: 99%
“…Moving from Titan's atmosphere down to Earth, biphenyl and larger polyphenyls -in addition to PAHs and carbonaceous dust particles [14,15] -have been detected in the plasma treatment of gaseous mixtures containing benzene [16,17] as well as in the radiolysis of liquid [18,19,20] and gaseous benzene [21]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…They later studied radiolysis of liquid benzene with protons, helium ions and carbon ions and found that the yield of biphenyl is independent of radiation type (La Verne and Araos, 2002). Biphenyl is the predominant single hydrocarbon product in the radiolysis of pure liquid benzene.…”
Section: Formation Of Polyphenyls From Benzenementioning
confidence: 99%